Update on scrofuloderma - Marianto Marianto; Hartono Kosim; Pande Agung Mahariski; Paulus Mario Christopher (DiscoverSys Inc, 2019)
Tuberculosis is one of the most significant diseases which causes death worldwide. TB infection is assumed to infect the lungs only from a general perspective. In fact, TB infection also causes lesions on the skin. Scrofuloderma, as one of the most common types of cutaneous tuberculosis, often misdiagnosed and managed improperly due to its similarity with abscess. In addition, there were still no national and international guidelines for scrofuloderma. This review to give insights and review about an update in the basic principle of scrofuloderma and management.